Non-Muslim Customers' Perceptions on Sharia Banking Services: Evidence from Bank Muamalat Indonesia - Wardoyo Putra, Rizky Iman Perkasa; Muh Shadiqul Fajri AF (The Es Economics and Entrepreneurship, 2023)
This research aims to find out and explore the implications of sharia banking service quality in increasing loyalty among non-Muslim customers by taking a sample of non-Muslim customers at Bank Muamalat Indonesia Makassar Branch. This type of research uses qualitative research that is explanatory in nature. Primary data was obtained from observations and interviews with 8 (eight) respondents consisting of 6 non-Muslim customers and 2 employees. The research results concluded that non-Muslim customers' perceptions of banking services at Bank Muamalat were quite good. They consider Bank Muamalat to provide services that are fast response, informative and have a sense of empathy. Bank Muamalat provides the same service standards to all customers, both Muslim and non-Muslim. The mobile banking facilities owned by Bank Muamalat provide many conveniences to customers so that the informants assess that the service facilities owned by Bank Muamalat can compete with conventional banks in Indonesia.